1997
DOI: 10.1038/sj.sc.3100399
|View full text |Cite
|
Sign up to set email alerts
|

Four year experience with the AO Anterior Thoracolumbar Locking Plate

Abstract: For decades spinal surgeons have attempted to design simple, single stage anterior internal ®xation systems for the thoracic and lumbar spine. Early devices presented both biomechanical and technical problems. The AO Anterior Thoracolumbar Locking Plate (ATLP) was designed to solve some of the problems encountered with early anterior instrumentation. The ATLP system is constructed in Commercially Pure titanium. It is a low pro®le device indicated for use for unstable burst fractures in the anterior column; met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Secondly, axially loaded locking screws subjected to cantilever bending are biomechanically superior to non‐locking screws, thus reducing risk of loosening. Locking plates have been reported to be safe in the management of thoracolumbar conditions in people, including degenerative disease between T10 and L5 (Thalgott and others 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, axially loaded locking screws subjected to cantilever bending are biomechanically superior to non‐locking screws, thus reducing risk of loosening. Locking plates have been reported to be safe in the management of thoracolumbar conditions in people, including degenerative disease between T10 and L5 (Thalgott and others 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The different implants are varying in the number of fixation points, modes of screw anchorage and number or type of screw connection (polyaxial vs. angular stable). Positive experiences with height adjustable implants lead to the development of in situ expandable and reducible plates to correct kyphotic spinal angulations or deformities after spinal tumours or fractures [31]. Encouraging results with locking plates in fracture treatment of extremities lead to the application of ''angular stable systems'' for the thoraco-lumbar spine [31].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Huang et al analyzed various configurations of anterior vertebral double screw fixation and found that triangulation of two anterior vertebral screws (22°inter-section angle) without penetration of the cortex achieved pullout strengths similar to that of two-parallel doublecortical screws. 19 Locking-head screws act mechanically as an angular stable, unitary implant with its connecting device and have significantly increased the rigidity of unicortical screw-plate systems initially and after cyclic loading in cervical vertebrae.…”
mentioning
confidence: 98%